The long road to Annapolis : the founding of the Naval Academy and the emerging American republic - Leeman, William P. (UPCC book collections on Project MUSE., 2010)
The United States established an academy for educating future army officers at West Point in 1802. Why, then, did it take this maritime nation 43 more years to create a similar school for the navy? Leeman examines the origins of the United States Naval Academy and the national debate that led to its founding. Considering the development of the naval officer corps in relation to American notions of democracy and aristocracy, Leeman's analysis sheds new light on the often competing ways Americans perceived their navy and their nation during the first half of the nineteenth century.